Should we look for celiac disease among all patients with liver function test abnormalities? - Mohammad Hassan Emami; Marzieh Hashemi; Soheila Kouhestani; Hajar Taheri; Somayeh Karimi (International Journal of Preventive Medicine, 2012)
Background: Celiac disease (CD) has been found in up to 10% of the patients presenting with unexplained abnormal liver function tests (LFT). As there is no precise data from our country in this regard, we investigated the prevalence of CD in patients presenting with abnormal LFT. Methods: From 2003 to 2008, we measured IgA anti-tissue transglutaminase (t-TG) antibody (with ELISA technique) within the first-level screening steps for all patients presenting with abnormal LFT to three outpatient gastroenterology clinics in Isfahan, IRAN. All subjects with an IgA anti-tTG antibody value of >10 μ/ml (seropositive) were undergone upper gastrointestinal endoscopy and duodenal biopsy. Histopathological changes were assessed according to the Marsh classification. CD was defined as being seropositive with Marsh I or above in histopathology and having a good response to gluten free diet (GFD). Results: During the study, 224 patients were evaluated, out of which, 10 patients (4.4%) were seropositive for CD. Duodenal biopsies were performed in eight patients and revealed six (2.7%) cases of Marsh I or above (four Marsh IIIA, two Marsh I), all of them had good response to GFD. The overall prevalence of CD among patients with hypertransaminasemia, autoimmune hepatitis, and cryptogenic cirrhosis was determined as 10.7% (3/28), 3.4% (2/59), and 5.3% (1/19), respectively. Conclusion: Serological screening with IgA anti-tTG antibody test should be routinely performed in patients presenting with abnormal LFT and especially those with chronic liver diseases including hypertransaminasemia, autoimmune hepatitis, and cryptogenic cirrhosis.